Intergenerational consequences of violence: violence during pregnancy as a risk factor for infection in infancy - Blumrich, Lukas; Sousa, Braian Lucas Aguiar; Barbieri, Marco Antônio; Simões, Vanda Maria Ferreira; da Silva, Antonio Augusto Moura; Bettiol, Heloisa; Ferraro, Alexandre Archanjo (Frontiers in Global Women's Health, 2024)
Introduction Psychosocial stress during pregnancy has long-lasting and important consequences in the following generations, as it can affect intrauterine development. The impact on the developing immune system is notoriously important due to the associated morbidity and mortality in the first years of life. Little attention has been given to the role of violence during pregnancy (VDP), especially its impact on infant infectious morbidity. Methods We analyzed data from two Brazilian birth cohorts (n = 2,847) in two distinct cities (Ribeirão Preto and São Luís), collected during pregnancy and at the beginning of the second year of life. The association between VDP and infection in infancy was analyzed with structural equation modeling, using the WHO-VAW questionnaire as exposure and a latent variable for infection as the outcome. Results VDP was reported by 2.48% (sexual), 11.56% (physical), and 45.90% (psychological) of the mothers. The models presented an adequate fit. In the city of São Luís, VDP was significantly associated with the latent construct for infection (standardized beta = 0.182; p = 0.022), while that was not the case for the Ribeirão Preto sample (standardized beta = 0.113; p = 0.113). Further analyses showed a gradient effect for the different dimensions of the exposure, from psychological to physical and sexual violence. Conclusion Our results suggest an association of VDP with infant morbidity in a poorer socioeconomic setting, and highlight the importance of considering the different dimensions of intimate partner violence. These findings may have important implications for the comprehension of global health inequalities and of the effects of gender-based violence.